Degradation of Organic Matter using Microbubble Diffuser - Wan Karimah Binti Wan Zid, Wan Karimah (Universiti Teknologi Petronas, 2006)
Aeration in biological wastewater treatment is where air is introduced to the aeration tank for mixing purposes and to enhance biological growth. Air or oxygen is supplied to the activated sludge by aerators. Fine bubble diffusion is a subsurface form of aeration in which air is introduced in the form of fine bubbles built from porous materials. However, in an attempt to increase the efficiency of biological treatment of wastewater, the performance of fine and micro bubble diffusion aeration systems was investigated in this study. The study evaluated the effectiveness of the micro bubble diffuser compared to the millimeter bubble diffuser in the treatment of municipal wastewater. Two batch reactors of size 140xl4Ox600 mm were fabricated. Porous sintered glass with porosities of 10-16 micron was used to produce the micro bubbles. Perforated aluminum disc of 3 mm thick with pore diameters ranging from 0.1-0.4 mm was fabricated to produce millimeter size air bubbles. Compressed air at a pressure of 63 kPa was forced through the diffusers from the bottom of the reactor at a flow rate of 2.5 L/min. Seed biomass for the wastewater treatment was obtained from a University Technology of Petronas sewage treatment plant (STP). The raw wastewater for the batch study was also taken from the STP. The wastewater sample was treated for a detention time of 48 hours and repeated for two runs. Sampling were conducted at 3 hours and 6 hours, for the first and second run, respectively. The effectiveness of both diffusers was evaluated based on removals of chemical oxygen demand (COD), and soluble chemical oxygen demand (SCOD). From the study it was found that the micro bubble diffuser has higher effectiveness in removing COD and SCOD with the average reaction coefficient k, of 0.041 and 0.0595, respectively. However, the average reaction coefficient k, for COD and SCOD using millimeter bubble diffuser was found to be 0.0275 and 0.044, respectively. The average removal of COD was found to be 86.8 % and 80.4 % for the micro bubble and millimeter bubble diffusers, respectively. The average removal of SCOD was found to be 90.9% and 75.1% for the micro bubble and millimeter bubble diffusers, respectively. It was also found that the micro bubble diffuser and millimeter bubble diffuser could saturate distilled water to 9.67 mg/L in 22 minutes and 94 minutes, respectively. As a conclusion, micro bubble diffuser was found to be efficient in the degradation of organic matter.